Consistent Nighttime Atomic Oxygen Concentrations From O2 A‐band, O(1S) Green‐Line, and OH Airglow Measurements as Performed by SCIAMACHY - Yajun Zhu; Martin Kaufmann (Geophysical Research Letters)
Abstract A new atomic oxygen data set was derived from nighttime SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) O2 A‐band measurements. It is compared to atomic oxygen obtained from SCIAMACHY O(1S) green‐line and OH(9‐6)‐band measurements. The three data sets are considered independent of radiometry and, to some extent, methodology. A detailed comparison of atomic oxygen retrieved from these three nightglow measurements is reported for the first time. The agreement of absolute values within 15% supports the current understanding of the photochemistry of the three atomic oxygen proxies involved. As an alternative approach, the O2 A‐band model recently proposed by Kalogerakis (2019) is used as well. It is striking that the SCIAMACHY data sets using different atomic oxygen proxies and mostly independent methodology agree much better with each other than with SABER data.